PENGEMBANGAN MEDIA LITERASI DIGITAL BERBASIS CERITA RAKYAT BERORIENTASI PADA NILAI KEARIFAN LOKAL - Kirom, Sabitul; Fadilla, Muchammad Kevin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Enhancing digital literacy in elementary schools necessitates the use of engaging, interactive, and contextually relevant media. Nevertheless, the creation of digital literacy media that incorporates local folktales and traditional wisdom has not been widely explored, especially within the educational framework of Blitar. This research seeks to create digital literacy media that is grounded in folk tales reflecting Blitar’s local values and to evaluate its feasibility, practicality, and effectiveness for literacy learning among students. The study uses the Research and Development method following the ADDIE framework. The participants in this research include elementary school students, teachers, and expert validators, such as content specialists and media specialists. Findings indicated that the media received validation scores of 93% from subject matter experts and 92% from media experts. The practicality assessment, derived from feedback from both teachers and students, was categorized as “very high,” whereas the effectiveness evaluation showed an improvement in students’ digital literacy skills, rising from 72 to 86. Therefore, the digital literacy media, inspired by folk tales and focused on the local wisdom of Blitar, is deemed suitable, practical, and effective for use in educational settings.